Synthesis, characterization and reactivity of iron- and cobalt-pincer complexes. (16th August 2016) - Smith, Ashleigh D.; Saini, Anu; Singer, Laci M.; Phadke, Neha; Findlater, Michael
Graphical abstract: Two PONOP-ligated Fe(II) and Co(II) complexes have been prepared and characterized. Treatment of either complex with NaBEt3 H affords catalytically competent earth abundant species capable of the hydrosilylation of aldehydes and ketones at room temperature. Abstract: The tBu PONOP (2, 6-bis(di- tert -butyl-phosphinito)pyridine) complexes of iron and cobalt, ( tBu PONOP)FeCl2 (1 ) and ( tBu PONOP)CoCl2 (2 )) have been prepared. Both complexes are paramagnetic and the solid-state structures of 1 and 2 were determined by single crystal X-ray diffraction studies. Analogous Fe and Co complexes of the tBu PNP (2, 6-bis(di- tert -butyl-phosphinomethyl)pyridine) ligand (3 and 4, respectively) were prepared to allow comparison between the closely related pincer ligands in the hydrosilylation of carbonyl moieties. All four complexes were found to be catalytically active when treated with NaBEt3 H, which was assumed to generate a metal-hydride species in-situ.